Implant prosthodontics : protocols and techniques for fixed implant restorations - Schoenbaum, Todd R. (Batavia, IL Quintessence Publishing Co, Inc., 2022)
Leaves the surgery to the surgical textbooks and instead focuses on the tools, techniques, tips, and tricks for successfully RESTORING dental implants from start to finish"-- |c Provided by publisher.
Includes bibliographical references and index.
Keywords: Dental Prosthesis Repair -- methods; Prosthodontics -- methods; Dental Prosthesis, Implant-Supported -- instrumentation; Dental Implants